Estimating the nutritive value of cereal crop residues: Implications for developing feeding standards for draught animals - Reed, J.D.; Goe, M.R. (1989)
Reviews analytical methods for the determination of the nutritive value of crop residues. Gives example on the accuracy of different methods in determining digestibility and of the factors affecting it. Highlights different management practices for feeding cereal crop residues to draught animals.